OPTIMIZATION OF DESIGN PARAMETERS FOR A VARIABLE FREQUENCY 3-PHASE INDUCTION MOTOR - APPLANAIDU, VISHNUV ARTHA (Universiti Teknologi PETRONAS, 2009)
This report describes the method of optimizing a variable frequency 3-phase Induction Motor. The objective of this project is to come up with a final design of a 3-phase induction motor that is optimum in weight and cost and maximum in efficiency (weight and cost) without violating the constraints provided. The design of induction motor chosen for this purpose is a squirrel cage design motor as it is more robust and is widely used in the industry. C-language is used to describe the design of the machine. The machine design mainly involves non linear equations such as the magnetizing current flows and motor losses . The objective function achieved from the design are cost, efficiency and weight. The optimization technique used to optimize this objective functions is Genetic Algorithm (GA) which is a Non -Linear Programming technique. Twelve (12) design variables are identified and used in the design process. The objective of this project is to come up with the optimized variable which produces the highest motor efficiency, minimum weight and cost. The results of the optimized values will be compared with the values obtained before optimizing. The comparison is shown in scatter line graph. The final design obtained is the improved the improved version of the design parameters compared with the one used as the input to the optimizing program.